Myocarditis in COVID-19 – Epidemiology, Pathophysiology, Diagnosis, Treatment and Clinical Outcomes - Walkowski, Radoslaw; Wasiniewska, Weronika; Kosek, Szymon; Klonowska, Justyna; Barański, Marcin; Kandefer, Tomasz; Sroka, Maria Izabela (Quality in Sport, 2025)
Myocarditis is a rare inflammatory disease affecting the myocardium and is caused by a variety of factors – medications, toxins, viruses and other processes that can include the heart muscle. It presents with multiple symptoms and can lead to heart failure and in some cases even sudden death. The diagnosis of myocarditis especially in COVID-19 poses many challenges. In regards to SARS-CoV-2 the post-infection myocarditis is more common, however there were some cases of post-vaccination myocarditis present. Treatment strategies are primarily supportive and focused on battling the symptoms. In this article we focused on research about pathophysiology, clinical presentation, diagnosis, treatment and long-term effects of COVID-19 on the heart.